Substantial hysteresis in emergent temperature sensitivity of global wetland CH4 emissions - Chang, Kuang-Yu; Riley, William J.; Knox, Sara H.; Jackson, Robert B.; McNicol, Gavin; Poulter, Benjamin; Aurela, Mika; Baldocchi, Dennis; Bansal, Sheel; Bohrer, Gil; Campbell, David I.; Cescatti, Alessandro; et al. (Springer Nature, 2021)
Wetland methane (CH4) emissions (FCH4) are important in global carbon budgets and climate change assessments. Currently, FCH4 projections rely on prescribed static temperature sensitivity that varies among biogeochemical models. Meta-analyses have proposed a consistent FCH4 temperature dependence across spatial scales for use in models; however, site-level studies demonstrate that FCH4 are often controlled by factors beyond temperature. Here, we evaluate the relationship between FCH4 and temperature using observations from the FLUXNET-CH4 database. Measurements collected across the globe show substantial seasonal hysteresis between FCH4 and temperature, suggesting larger FCH4 sensitivity to temperature later in the frost-free season (about 77% of site-years). Results derived from a machine-learning model and several regression models highlight the importance of representing the large spatial and temporal variability within site-years and ecosystem types. Mechanistic advancements in biogeochemical model parameterization and detailed measurements in factors modulating CH4 production are thus needed to improve global CH4 budget assessments.
Keywords: wetlands; methane; temperature sensitivity; global carbon budgets; climate changes